THE ROLE OF GUT MICROBIOTA DYSBIOSIS IN THE PATHOGENESIS AND PROGRESSION OF CHRONIC INFLAMMATORY BOWEL DISEASE IN CHILDREN (LITERATURE REVIEW) - Farmonov Samandar Anvar o‘g‘li; Ro‘ziyev Javlonbek Orifjon o‘g‘li; Zayniddinov Og‘abek Farxod o‘g‘li; Egamberganova Mohimjon Mahmudjon qizi; Saparklicheva Ayzada Rahman qizi (TADQIQOTLAR, 2026)
Abstract   Chronic  inflammatory  bowel  disease  (IBD),  encompassing  Crohn’s  disease (CD)  and  ulcerative  colitis  (UC),  represents  a  growing  burden  in  the  pediatric population,  with  gut  microbiota  dysbiosis  increasingly  recognized  as  a  central pathogenic  driver.  This  review  synthesizes  current  evidence  linking  gut  microbial imbalance—characterized  by  reduced  diversity,  depletion  of  short-chain  fatty  acid (SCFA)-producing  commensals,  and  expansion  of  pro-inflammatory  species—to mucosal  barrier  dysfunction,  immune  dysregulation,  and  chronic  intestinal inflammation  in  children.  Persistent  dysbiosis  activates  innate  immune  pathways including Toll-like receptors (TLRs) and the NLRP3 inflammasome, perpetuating a cycle  of  epithelial  injury,  cytokine  release,  and  fibrotic  remodeling.  Early-life disruptions to microbial colonization, including antibiotic exposure, cesarean delivery, and  formula  feeding,  further  predispose  children  to  IBD  onset.  Despite  growing mechanistic  understanding,  pediatric-specific  longitudinal  microbiome  data  remain scarce, highlighting the urgent need for validated biomarkers and microbiota-targeted therapeutic  strategies.  Interventions  such  as  dietary  modulation,  fecal  microbiota transplantation  (FMT),  and  probiotic  supplementation  offer  promising  avenues  to restore microbial homeostasis and preserve intestinal integrity in affected children.